BUDMERGO: MUSIC VIBRATION CONDUCTING DEVICE FOR THE HEARING IMPAIRED - Wrahatnala, Bondet; Aji Manggala, Bondan; Sri Kuncoro, Jonet; Kapri, Riana; Nurhadi, Muhamad; Arya Pradipta, Dana Adi; Budiyanto, Agus; El Java, Joi (Universitas Negeri Surabaya, 2025)
This article examines performing arts technology in the form of a musical vibration delivery device called Budmergo for deaf people. This activity optimizes the work of the Budmergo tool as an expression tool in the context of intermedia performance art activities. As a result, it hopes to involve deaf people in art performances according to their characteristics and realize a creative space for art that favors their unique abilities and needs. This activity is based on the mindset that each individual can absorb and internalize the phenomena around them through different means and media while also expressing them independently in art. The general objective of this activity is to conduct an art technology study of the Budmergo tool to (1) find knowledge, methods, and art media that can optimize the art activities of deaf people, (2) evaluate the technology of the Budmergo tool (3) socio-psychologically be able to raise the dignity of deaf people, considering that the participatory art creation model is full of human values with participant involvement, and (4) get recommendations for the development of unique art performance technology for deaf people.